Spatiotemporal Distribution of Wine Grape Under Climate Change in Northwestern China - Yanyan Liu; Xuejia Shi; Hongjuan Du; Mengjiao Jiang; Fang Li; Jing Wang; Xiaoyu Zhang (Ecology and Evolution)
ABSTRACT The favorable terroir of China's northwest region provides an ideal environment for the cultivation and thriving growth of grapes. However, climate change threatens to alter the optimal grape‐growing regions, presenting considerable challenges to the local wine making industry. To enhance the utilization of regional climate resources and refine the wine grape industry's spatial distribution, this study assessed the performance of nine climate models from the Coupled Model Intercomparison Project Phase 6 (CMIP6) in Northwestern China, simulated the future spatiotemporal distribution of wine grape. Results showed that EC‐Earth3 performed well in simulating temperature, precipitation, and interannual changes. Under the historical periods (1980–2014), the highly suitable areas for wine grapes were predominantly found in the eastern foothills of Helan Mountain in Ningxia, along the Yellow River in Wuhai and Linhe of Inner Mongolia, along the Qilian Mountains in Wuwei, Zhangye and Jiayuguan of Gansu, and along rivers and oases in the northern foothills of Tianshan Mountains, Ili River Valley, Tuha Basin, Yanqi Basin, Aksu, Muzart, and Kashgar of Xinjiang. Compared with historical periods, the highly and moderately suitable areas were expected to expand under SSP245 and SSP585. Nevertheless, the overall pattern of spatial distribution was not anticipated to experience substantial alterations. In the next 50 years (2055–2085), the suitable areas under SSP245 scenario would be higher than SSP585. Precipitation from July to September (pr79), soil pH (ph), elevation (dem), and near‐surface air temperature in January (tas1) were the main factors affecting the suitable areas of wine grapes. Further analysis revealed that a certain level of the near‐surface air temperature in January (tas1) contributed positively to the expansion of suitable areas. However, excessively high average temperatures in January and July tended to have a detrimental effect. A rise in winter temperature can foster a more favorable environment for wine grapes to overwinter. However, frequent summer heat waves and high winter temperatures caused by climate warming may have adverse effects.